A general attack model based on Android system vulnerability - Xihai DENG; Weimiao FENG; Luping MA; Ying LI (Dianxin kexue)
Various kinds of vulnerabilities in Android system bring great threats to the platform. The vulnerability exploitation technology,the security of mobile operating systems and the security of Android ecosystem have become a research focus in both industry and academia. The exploitation of several typical system vulnerabilities was analyzed, a general model of Android system vulnerability exploitation was proposed, and a novel evaluation framework for the effectiveness of vulnerability exploitation was presented. The experiment result shows that the general model is able to accurately describe the process of hacker attacks using Android system vulnerabilities. Furthermore, the evaluation framework can assess the influence of system vulnerabilities on the security of Android ecosystem.